2004
DOI: 10.1097/01.bcr.0000124788.38214.5f
|View full text |Cite
|
Sign up to set email alerts
|

Burns from Illegal Drug Manufacture: Case Series and Management

Abstract: This case series presents our experience with burns sustained while manufacturing illegal drugs. All adult burn admissions in an 18-month period were retrospectively reviewed. All patients suspected of sustaining burns from illegal drug manufacture were contacted. Information regarding the burn mechanism was sought. Nine of the 64 adult burn admissions were caused by explosions during the manufacture of cannabis oil. Young males with hand and face burns were heavily represented. First-aid treatment was often i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Fear of incrimination often leads amateur producers to be reticent in seeking medical care and to attribute the damage to some other cause. 3,4 Although blasting may be an appealing project for a young cannabis user, the safety risks have been described as comparable to those of manufacturing methamphetamine.…”
Section: Bryan Lee Miller Phd Bmentioning
confidence: 99%
“…Fear of incrimination often leads amateur producers to be reticent in seeking medical care and to attribute the damage to some other cause. 3,4 Although blasting may be an appealing project for a young cannabis user, the safety risks have been described as comparable to those of manufacturing methamphetamine.…”
Section: Bryan Lee Miller Phd Bmentioning
confidence: 99%
“…3,5,[7][8][9] We found converging evidence from 190 reported cases of patients with cannabis burns suggesting that (a) these patients were young (mean 43 yr), (b) men were overrepresented (male to female ratio 9.6:1), (c) the patients sustained burns over a large percentage of their total body surface area (23.9%), (d) they required extensive surgical management (skin grafting in 55.3% of cases) and (e) they spent a significant amount of time (mean 28.3 d) in the burn unit. 3,5,[7][8][9] To place these findings in context, for the 205 033 burn cases reported from 96 hospitals in the American Burn Association's National Burn Repository (NBR) from 2006 to 2015, the male to female ratio was 2.1:1. Although an average percentage of total body surface area burned was not reported, more than 75% of total burn sizes in this data set were less than 10% of total body surface area and 90% of all cases had a burn surface area of 20% or less.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is common to reports describing illegal drug manufacturing. 7,8 In a case series from New Zealand, the authors found that only 2 out of 9 patients confessed to cannabis oil extraction being the cause of their injury on their own. 7 Second, it is possible that we missed minor injuries that were not referred to our tertiary burn clinic, which might weaken our finding that cannabis oil burns are more severe than burns in general.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Explosions have been reported in numerous states including those in which dabs can be easily purchased. 9 , 11 – 13 It is perhaps the aspiration to utilize less desirable portions of the plant (ie, “trim”) that motivates amateurs to attempt this process in legalization states (as BHO is already readily available at distributors at a price that is not restrictive); Colorado has seen an increase in BHO-related burns in the last several years 9 (we define BHO-related burns broadly to include damage that results from accidents during the manufacturing process and from the blowtorch that is frequently used during administration). Regardless of the regulatory status of marijuana in a state, home “blasting” is considered in most jurisdictions to carry the legal consequences of operating a drug lab with strict penalties due to the risk of explosion.…”
Section: Butane Hash Oil – the “New” Old Form Of Marijuana Use Growinmentioning
confidence: 99%